Measuring adolescent sense of belonging: development of an instrument incorporating gender, ethnicity, and age - Harrison, Shannon, author; Buchan, Victoria, advisor; Orsi, Rebbeca, committee member; Gandy, John, committee member; Canetto, Silvia, committee member (Colorado State University. Libraries, 2017)
Studies incorporating the Interpersonal Theory of Suicide (ITS) have largely excluded the association of adolescents with the ITS construct, thwarted belonging. A closer examination of the ITS was necessary, due to its potential for providing information regarding suicide risk. The purpose of this study was to develop a Sense of Belonging Measure, to examine whether and how the construct, thwarted sense of belonging, applied to adolescents, specifically by gender, ethnicity, and age group. Data (N = 10,148) from the National Comorbidity Survey-Adolescent Supplement (NCS-A, 2001-2004) was analyzed. Adolescents aged 13-18 completed the the survey. An exploratory factor analysis and Cronbach's alpha testing determined that the variables in the Sense of Belonging Measure reliably measured the concepts that the literature identified as being related to adolescent belonging. A three way analysis of variance (ANOVA) produced statistically significant main effects of age groups, and of ethnicity, on sense of belonging. An unexpected statistically significant interaction effect of gender and ethnicity on sense of belonging was produced. It is recommended that this measure be clinically tested in mental health settings, to further determine the utility of the construct "thwarted sense of belonging," in its application to adolescents.
Keywords: age; ethnicity; instrument; belonging; adolescent; gender